2017
DOI: 10.3390/en10070870
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wind Energy Yield and Grid Utilisation with Continuous Feed-In Management

Abstract: This paper presents a study to assess how wind turbines could increase their energy yield when their grid connection point is not strong enough for the rated power. It is state of the art that in such situations grid operators impose feed-in management on the affected wind turbines, i.e., the maximum power is limited. For this study a 5 MW wind turbine is introduced in a small grid that has only limited power transfer capabilities to the upstream power system. Simulations of one particular day are conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 3 publications
1
33
0
Order By: Relevance
“…The 1 st Eigenmodes model of a wind turbine represents the generator-converter unit as a first order low pass filter (PT1). In the previous study on continuous FIM [5] the time constant of this PT1 filter (T_PT1_geno_substi [21]) was set to 150 ms, which is a reasonable value for normal power control of a WT. In the inertial response study shown here, this time constant has to be reduced to a lower, but yet realistic value, to allow more rapid power variations as this is needed for effective inertial response.…”
Section: Power Controllermentioning
confidence: 99%
See 4 more Smart Citations
“…The 1 st Eigenmodes model of a wind turbine represents the generator-converter unit as a first order low pass filter (PT1). In the previous study on continuous FIM [5] the time constant of this PT1 filter (T_PT1_geno_substi [21]) was set to 150 ms, which is a reasonable value for normal power control of a WT. In the inertial response study shown here, this time constant has to be reduced to a lower, but yet realistic value, to allow more rapid power variations as this is needed for effective inertial response.…”
Section: Power Controllermentioning
confidence: 99%
“…Consequently, FIM becomes necessary in situations of high wind speeds, and/or very low local consumption in the campus grid. The FIM controller, which is shown in Figure 6 addresses the thermal loading of the transformer as well as VC [5].…”
Section: Continuous Feed-in Management Controlmentioning
confidence: 99%
See 3 more Smart Citations